The Seven Eyes of God - Yogev, Jonathan (Vetus Testamentum, 2019)
The image of the stone with seven eyes in the book of Zechariah 3-4 is very puzzling, and has been interpreted in various ways. In this study I will suggest that the most logical interpretation of this image lies in the Babylonian kalû ritual and the well-known mythological Sibittu iconography that was familiar and accepted by the returning Babylonian exiles. This iconography was chosen for a specific reason, and then was given a new identity by the prophet, probably as part of a certain agenda.